Atlas of Amazing Architecture: The Most Incredible Buildings You've (Probably) Never Heard of - Allen, Peter; Hanaor, Ziggy (London UK Cicada Books Ltd., 2021)
"This atlas of architectural wonders eschews the classic children's book fare of the Pyramids and the Taj Mahal, and instead takes a broader view of what constitutes amazing architecture. Buildings include: the Jameh mosque of Isfahan? in Iran, Native American plank houses in New Mexico, Stave Churches in Norway, The Djinguereber mosque in Mali, and extraordinary 18th century wooden churches on Kizhi Island, Russia. Over 50 buildings span all the continents equally throughout history. Each of these buildings is visually striking and architecturally noteworthy; they introduce new engineering technologies or define a movement or capture the essence of a moment in human history. They epitomise the ambition and vison of an architect or a patron. But although most of them have been recognized by UNESCO or other agencies, they are not part of the main Western architectural canon. This book seeks out a more diverse, inclusive approach to what constitutes amazing architecture, and presents it with fresh illustration and clear, punchy text"--.
Introduction -- Neolithic monuments Europe, 4000-2000 BCE -- Ziggurat of Ur Iraq, 2100 BCE -- Meroe Pyramids Sudan, 800 BCE-100 CE -- Shanxi Hanging Monastery China, 491 CE -- Hagia Sophia Turkey, 537 CE -- Anji Bridge China, 595-605 CE -- Horyu-ji Temples Japan, 607 CE -- Jameh Mosque of Isfahan Iran, 771-1997 CE -- Chand Baori India, 800 CE -- Chartes Cathedral France, 1194-1220 -- Bogrund Stave Church Norway, ca. 1200 -- Church of St George Ethiopia, ca. 1200 -- Doge's Palace Italy, 1340-1424 -- Djinguereber Mosque Mali, 1327 -- Ayutthaya Thailand, 1350-1767 -- Little Moreton Hall United Kingdom, 1504-1610 -- Traditional Japanese architecture -- Kizhi Pogost Russia, 1714 -- Casbah of Algiers Algeria, 17-18th centuries -- Hwaeseong Fortress South Korea, 1794-1796 -- Brighton Pavilion United Kingdom, 1787-1823 -- Neuschwanstein Castle Germany, 1869-1892 -- Chief Waka's House Canada, ca. 1890 -- Casa Batllo Spain, 1904-1906 -- Tatlin's Tower Russia, 1919 -- Dar al Hajar Palace Yemen, 1920 -- Rietveld Schröder House Netherlands, 1924 -- Architecture for World's Fairs -- University City, Mexico Mexico, 1949-1952 -- Cuban National Art Schools Cuba, 1961-1965 -- Sea Ranch USA, 1963-1965 -- FIDAK Senegal, 1975 -- New models for living -- Hundertwasser House Austria, 1983-1985 -- Guggenheim Bilbao Spain, 1991-1997 -- Jewish Museum, Berlin Germany, 1992-1999 -- New models for worship -- Airport architecture -- SGAE Headquarters Spain, 2008 -- Hideaways.
Hardcover
Includes index.
new kids book 2025 spring.
Ages 07-17
2nd Grade-12th Grade
Keywords: Architecture; Architecture -- Juvenile literature; Historic sites -- Juvenile literature; Historic buildings -- Juvenile literature